Castaways of the Flying Dutchman - Jacques, Brian; Schoenherr, Ian (New York : Philomel Books, 2001)
In 1620, a boy and his dog are rescued from the doomed ship, Flying Dutchman, by an angel who guides them in travelling the world, eternally helping those in great need.
770
Accelerated Reader AR
Keywords: Heroes -- Fiction; Dogs -- Fiction; Angels -- Fiction; Flying Dutchman -- Fiction